2018
DOI: 10.1039/c8cp05574b
|View full text |Cite
|
Sign up to set email alerts
|

Thousand-atom ab initio calculations of excited states at organic/organic interfaces: toward first-principles investigations of charge photogeneration

Abstract: Electron and hole wave functions of low-lying and hybridized interfacial charge-transfer states across the pentacene/C60 interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The expression denotes that electron correlation and orbital relaxation within a target fragment are treated at the GW level, whereas the associated induced polarization energy of an entire system is computed at the static COHSEX level. We have shown that the static COHSEX can appropriately describe the solid-state effects on electronic states 9 and expect that the combined GW and static COHSEX approach can provide a reasonable approximation for a weakly interacting molecular system. The FMO-GW quasiparticle energy of the fragment is calculated in a perturbation manner as follows:…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…The expression denotes that electron correlation and orbital relaxation within a target fragment are treated at the GW level, whereas the associated induced polarization energy of an entire system is computed at the static COHSEX level. We have shown that the static COHSEX can appropriately describe the solid-state effects on electronic states 9 and expect that the combined GW and static COHSEX approach can provide a reasonable approximation for a weakly interacting molecular system. The FMO-GW quasiparticle energy of the fragment is calculated in a perturbation manner as follows:…”
Section: Methodsmentioning
confidence: 98%
“…Therefore, we employed the atomic structure of the edge-on configuration of the PEN/C 60 bilayer heterojunction, which was prepared using molecular dynamics (MD) simulations. 9 respectively. The local interface structure is composed of 36 PEN and 15 C 60 molecules and thus contains 2196 atoms.…”
Section: B Application To Pen/c 60 Interfacementioning
confidence: 98%
See 3 more Smart Citations